The Effect of Follicle Stimulating Hormone (FSH) on Colony Formation of Ovine Spermatogonial Stem Cells in Vitro - Parviz Tajik; Mohammad-Reza Mokhber-Dezfuli; Nafise Alighazi; Peyman Rahimi-Feyli; Shiva Shafiei (مجله دانشکده پزشکی اصفهان, 2014)
Background: Spermatogonial stem cells (SSCs) are undifferentiated cells with special capabilities on the self-renewing and differentiation. Proliferation of SSCs is a primary requirement for the study of their characteristics and function in vitro. The aim of this study was to evaluate the effects of different concentrations of follicle stimulating hormone (FSH) on the colonization activity of ovine SSCs in a short-term in-vitro co-culture with sertoli cells.